COMPARISON OF INDONESIAN AND PHILIPPINE PUBLIC ADMINISTRATION REGULATIONS IN DEALING WITH AI DISRUPTION IN ASEAN - Azzahro, Syahda; Aminullah (International Journal of Multidisciplinary Reseach, 2026)
The adoption of Artificial Intelligence (AI) in the public sector has become the main engine of bureaucratic efficiency by 2026. This research aims to critically dissect the regulatory readiness and public administration capacity of Indonesia and the Philippines in welcoming ASEAN leadership 2026. Using a qualitative-comparative approach, this study compares policies such as Presidential Decree No. 82 of 2023 in Indonesia and the National AI Strategy Roadmap 2.0 in the Philippines. The results show that Indonesia excels in the availability of large public datasets through the SPBE system and the INA Digital portal, but still faces the challenges of rigid cross-sectoral coordination and AI regulations that are not yet legally binding. In contrast, the Philippines has demonstrated regulatory agility through a networked governance model and has mandated an Algorithmic Impact Assessment to mitigate the risk of algorithmic bias. The study concludes that synchronization between data sovereignty and international collaboration is crucial for modern bureaucracies in Southeast Asia to protect citizens' rights amid technological disruption.